Analisis Yuridis Akibat Hukum Kedudukan Anak Yang Lahir Dari Perjanjian Sewa Rahim (Surrogacy) Terhadap Ibu Pengganti Ditinjau Dari Perspektif Hukum Positif dan Hukum Islam - Zaharnika, R. Febrina Andarina; Erlina, Erlina (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
The development of assisted reproductive technology, particularly the practice of surrogacy, has given rise to various legal issues, especially concerning the legal status of children born through surrogacy and their legal relationship with the surrogate mother. In Indonesia, surrogacy is not explicitly regulated in statutory law, resulting in legal uncertainty regarding the civil status of the child and the rights and obligations of the parties involved. This issue becomes more complex when examined from the perspective of Islamic law, which has specific provisions concerning lineage (nasab), motherhood, and the validity of agreements. This research aims to analyze the legal consequences concerning the status of children born from surrogacy agreements in relation to the surrogate mother from the perspectives of positive law and Islamic law. The research method employed is normative legal research using statutory, conceptual, and comparative approaches. The data sources consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The results of the study indicate that from the perspective of Indonesian positive law, the practice of surrogacy is not legally recognized and contradicts statutory provisions in the fields of health and marriage law, rendering surrogacy agreements legally unenforceable. Consequently, the legal status of the child tends to follow the woman who gives birth, based on the principle of mater semper certa est. Meanwhile, from the perspective of Islamic law, surrogacy is generally considered impermissible as it leads to the mixing of lineage and contradicts the principle of clarity of descent. The child is attributed to the woman who gives birth rather than to the genetic mother. Therefore, both positive law and Islamic law place the surrogate mother as the party having a legal relationship with the child born through surrogacy.